Navigating Language Proficiency Challenges: Enhancing Business Presentations in Indonesian Vocational Higher Education - PARAMUDIA, Paramudia; AKHMAD, Akhmad; AMRI, Amri; FAHLEVI, Andi Rayhan (Politeknik Negeri Ujung Pandang, 2024)
This article explores the intricate landscape of language proficiency challenges faced by students in Indonesian Vocational Higher Education, with a specific focus on refining their skills for effective business presentations. As English proficiency emerges as a critical asset in the globalized business arena, understanding the nuanced obstacles encountered by students becomes paramount. Through a mixed-methods research approach employing questionnaires and interviews, the study aims to identify specific language challenges and explore tailored strategies for improvement. The research delves into students' experiences, addressing vocabulary proficiency, pronunciation concerns, and the impact of language proficiency on the overall effectiveness of business presentations. By shedding light on these challenges and seeking insights from students, this article aims to contribute practical recommendations for enhancing language proficiency, bridging the gap between academic preparation and the demands of professional business communication in the Indonesian Vocational Higher Education context